(untitled) - Platt, Charles (Sebastopol, CA, 2013)
This first book of a three-volume set includes key information on electronics parts for your projects—complete with photographs, schematics, and diagrams. You’ll learn what each one does, how it works, why it’s useful, and what variants exist. No matter how much you know about electronics, you’ll find fascinating details you’ve never come across before.
Keywords: Thiết bị và thiết bị điện tử,Electronic apparatus and appliances